Rancang Bangun Sistem E-Invoice Dengan Metode Pieces Berbasis Web Pada PT.XYZ - Migunani, Migunani (LPPM Universitas Sains dan Teknologi Komputer, 2023)
In company activities, data input is very important for a company. The data input activity itself is one of the factors that really supports the recording of company income and expenses. Invoice is a collection letter issued by the seller to the buyer or in this case the customer according to the agreement stated in the purchase order. Companies issuing invoices aim to show all types of goods, types of goods. The pieces method is a system that is used for analysis of work systems in a company or organization. The PIECES framework analysis method itself is an information system analysis method commonly used to analyze an information system in a computer-based company, where there are several criteria in the test, including Performance, Information, Economy, Control, Efficiency and Service. Information system for making e-invoices that is carried out with the aim of knowing the process of making e-invoices in CV. XYZ. The results of the study obtained a comparison of manual systems with information systems showing that web-based information systems are more profitable in managing company administration. The following are the results of system testing using a black box on the implementation of a web-based e-invoice creation information system on CV. XYZ. With the design of this E-Invoice information system, the admin can make it easier to make transactions for making notes/bills because it is computerized. The E-Invoice information system can make it easier for cashiers to find bills that have been paid and have not been paid. The E-Invoice information system makes it easy for cashiers to calculate the amount of invoices, which have been paid or which have not been paid because the E-Invoice information system has been computerized. The E-Invoice information system makes it easy for admins to make financial reports.